54 Busting some myths of online delivery of palliative care education. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Gallard, Sian; Rawlinson, Fiona; Stacey, Mark; Harris, Dylan; Griffiths, Jo; Hayes, Jo; Grose, James; Richards, Jo
Abstract : Background/Introduction: There is an urgent need to continue palliative care professional development (CPD) for all those delivering health care, especially in view of health needs of the population currently affected by the Covid-19 pandemic. Face to face teaching, whilst preferable to date, has not been possible. The face to face interaction at the start of a Masters course in Palliative medicine was transitioned to virtual learning. We explored the impact of using technology on the learning experience of participants both in terms of comfort with the virtual environment and its impact on their learning Methods: Prospective evaluation of a redesigned face to face teaching programme. Participants were asked if the virtual learning environment or technology had impacted on their learning using a 5 point scale for each of the sessions. A further delayed evaluation is underway, to explore the continued impact of the sessions. Results: 13 sessions forming a 3 day programme were evaluated. 252 responses were received (45% response rate) 223/252 responded that all was well, 18/252 mentioned some technical difficulties but with no negative impact on learning, 8 mentioned technical issues which did impact on learning, 2 mentioned being uncomfortable with the virtual learning environment with no impact on learning and 1 person described being uncomfortable with negative impact.Results to date of the delayed evaluation have been received from 16 participants (response rate of 32%). Conclusions: Enabling virtual CPD to continue to skill and enable the health care workforce to deliver palliative care to patients is paramount, especially while Covid-19 restrictions to face to face gatherings continue. With attention to teaching techniques (delivery style, focused content and use of interaction), neither the technology or a virtual learning environment, negatively impact learning for the majority of students. Further exploration of prospective data is underway.